Partial splenic embolization in beta-thalassemia major: a case report - Meral, Adalet; Sevinir, Betül; Sadıkoğlu, Yurtkuran; Nacarküçük, Ergun; Günay, Ünsal (The Turkish Journal of Pediatrics, 2000)
Partial splenic arterial embolization was performed in a thalassemic child for hypersplenism manifested by splenomegaly, leukopenia, thrombocytopenia, and anemia requiring frequent erythrocyte transfusion. During a follow-up period of 11 months, his hematological parameters improved significantly and the spleen size decreased. Partial splenic embolization could be an alternative therapy to surgical splenectomy for thalassemic children with hypersplenism.
Keywords: splenic embolization; thalassemia